Antisemitism in Doubt: Historical and Methodological Reflections on Contemporary Europe - Morris-Reich, Amos (Zeitschrift für Pädagogik und Theologie, 2021)
In the attempt to find an Israeli approach to understanding the current European ambivalence towards Jews, this study focuses on the question of post-Holocaust anti-Semitism. It analyzes a specifically Israeli structure of experience of "schizophrenia" resulting from its decoupling of antisemitism from the Holocaust. It is shown that the justification of anti-Semitism has changed after the Holocaust. Thus, anti-Semitism has developed from a "cultural code" to a "semiotic problem". The article concludes that the two main forms of Israel's response to European anti-Semitism are inseparably linked to the question of whether Zionism ended with the establishment of the modern state of Israel and whether Israel is a "normal" state.